Prevalence of Vitiligo Among Patients in Baquba City - Mohammad Husain Al-Qayssi (Diyala Journal of Medicine, 2019)
Background: Vitiligo is an acquired, idiopathic, and worldwide common depigmentation disorder with an estimated prevalence from 0.1 to 2.5%. These numbers are based on clinical population studies and field research examining inhabitants of geographically enclosed areas.